2015
DOI: 10.1039/c5ta00724k
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial architectures based on a binary additive combination for high-performance Sn4P3 anodes in sodium-ion batteries

Abstract: Interfacial architectures based on the FEC + TMSP binary additive prevent the formation of Na15Sn4 with severe volume expansion and electrolyte decomposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 30 publications
1
65
0
Order By: Relevance
“…This finding reveals that NaF formed by FEC decomposition acts as a resistive layer for Na plating/stripping in the ultraconcentrated 5 M NaFSI-DME electrolyte. 17,22 We surmise that minimal amount of free (uncoordinated) DME in the ultraconcentrated 5 M NaFSI-DME electrolyte minimizes the formation of a resistive SEI layer via interaction of the electrolyte components with reactive Na metal. The impact of ultraconcentrated 5 M NaFSI-DME on the cycling stability at high C rates is shown in Figure 12d.…”
Section: Electrochemical Performances Of Na/ss Cells and Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…This finding reveals that NaF formed by FEC decomposition acts as a resistive layer for Na plating/stripping in the ultraconcentrated 5 M NaFSI-DME electrolyte. 17,22 We surmise that minimal amount of free (uncoordinated) DME in the ultraconcentrated 5 M NaFSI-DME electrolyte minimizes the formation of a resistive SEI layer via interaction of the electrolyte components with reactive Na metal. The impact of ultraconcentrated 5 M NaFSI-DME on the cycling stability at high C rates is shown in Figure 12d.…”
Section: Electrochemical Performances Of Na/ss Cells and Analysismentioning
confidence: 94%
“…[20][21][22][23][24][25][26][27] Nevertheless, the practical application of Na metal batteries is quite challenging because the high chemical and electrochemical reactivity of Na metal electrodes with organic liquid electrolytes leads to low Coulombic efficiencies and limited cycling performance. 20,[24][25][26] Severe electrolyte decomposition at the Na metal electrode results in the formation of a resistive and non-uniform surface film, leading to dendritic Na metal growth.…”
Section: Problems Of Na Metal Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] It has been recently reported that Sn 4 P 3 showed a synergistic Na-storage reaction where Sn and P atoms can react with Na to form Na 15 Sn 4 and Na 3 P, and that the resulting Na 15 Sn 4 alloy acts as a conducting pathway to activate the reversible Na-storage reaction of nonconductive Na 3 P particles while the well-dispersed Na 3 P phase provides a shield matrix to prevent the aggregation of the Na 15 Sn 4 / Sn nanoparticles.…”
Section: Introductionmentioning
confidence: 99%